Optimizing the Care and Management of Older Offenders: A Scoping Review. (22nd July 2021) - Hagos, Amanuel K; Butler, Tony G; Howie, Adam; Withall, Adrienne L
Abstract: Background and Objectives: The rapid increase in the number of older offenders in many countries presents unique challenges to both correctional and health care systems. In the absence of strong empirical evidence on effective interventions, identifying best practices can help optimize the care and management of this segment of the prisoner population. Research Design and Methods: We conducted a scoping review of care models, prison programs, and different interventions designed to improve the care and management of older offenders. We searched 5 bibliographic databases and other data sources including OpenGrey, agency documents, and government reports published until December 2020. This review employed commonly used steps for conducting a scoping review and applied additional tools to enhance the methodology. Results: After title and abstract screening and full-text review, a total of 34 studies were included in the analysis. Four themes emerged from the review: (a) institutional logics, (b) adaptations, (c) multidisciplinary teams, and (d) person-centered care and management. Discussion and Implications: Best practices identified in this review can help optimize the care and management of older offenders in mainstream prisons. Further action research is recommended to adapt and scale up the interventions.